O factor população no planeamento e condução das operações militares convencionais - Freitas, António (2016)
Este trabalho de investigação individual tem como tema “o factor população no planeamento e condução das operações militares convencionais”. Atendendo à vastidão de matérias que o tema abarca e às opiniões recebidas do orientador e de outros oficiais, alguns do Departamento de Operações do IESM, entendeu o autor delimitar a abordagem do tema às operações militares urbanas, onde é muito significativa a presença de população civil, e às operações de informação, nomeadamente operações psicológicas, informação pública e cooperação civil militar. A rápida urbanização está a concentrar a população no litoral e, em especial, em centros urbanos onde a aglomeração de pessoas é cada vez maior. Esta situação leva a admitir a forte possibilidade de, no futuro (mesmo a curto prazo), grande parte das operações militares vir a ocorrer em zonas urbanas. Neste trabalho faz-se uma abordagem ao teatro das operações (TO) urbanas, às suas diferentes vertentes e aos aspectos mais directamente ligados à população civil não combatente. Caracteriza-se um conflito em que as operações são extremamente exigentes e podem provocar importantes baixas e perda de equipamento, requerendo um forte empenhamento de capacidades e o controlo do TO. Refere-se os principais problemas que se deparam ao soldado ou ao fuzileiro e aos seus comandantes, aludindo à sua preparação para os enfrentar. As regras de empenhamento (ROE), sendo directivas para as forças militares que regulam o uso da força, e tendo como finalidade o cumprimento da missão, são alvo de análise, também sob uma perspectiva ética, e do estabelecimento de uma relação com o SOFA (Status of Forces Agreement), quando aplicável. Tendo em linha de conta o tema do trabalho, aprofundaram-se assuntos mais directamente ligados ao factor população no desenvolvimento do conflito urbano, tais como as operações de informação nas suas vertentes de operações psicológicas e da cooperação civil militar. Abstract: Rapid urbanization is changing the physical and political face of nations. Demographic studies indicate a vast increase in the number and size of urban areas throughout the world. This population concentration has ensured that many future military operations will be taking place in urban areas. The key to success in urban operations may lie in the ability to control the information environment and influence the thoughts and opinions of adversaries and non-combatants through information operations, in particular, psychological operations. Civil-military operations may be crucial to accomplishing operational objectives in urban warfare. It is common for an enemy, particularly one engaged in asymmetric warfare, to utilise the complex urban environment to generate combat power, especially when dealing with an opposing force which possesses more sophisticated technological weapon systems. In the military sense, urban centres are centres of gravity because they are psychologically symbolic, and economically and culturally powerful. They represent the hub of politics, culture, services, manufacturing and transport. As centres of gravity they are doctrinally significant military objectives in any conflict. In conflicts last century, and in the few years of this century, the Armed Forces conducted many of its operations in urban environments. Present political guidance, requires the Armed Forces to further develop its capacity to operate in urban terrain, increasingly in Joint and Combined environments. This requires Armed Forces to develop a modern system of doctrine, training, structures and equipment for urban operations. Historically, urban combat has been expensive in deaths of soldiers and non-combatants, destruction of infrastructure, consumption of military logistics resources, and often also in political terms in the domestic and international arena. Any revised or new urban combat system must endeavour to maximise combat effectiveness while conserving not only the combat force, but also non-combatants and urban infrastructure. Central in any combat system is the soldier - the human operator within that system. The paper describes the urban operations environment from the commanders and soldiers perspective, and it then considers the development of a system for conducting urban operations. It also characterises the urban environment as comprising three subsystems, physical, functional and social. The physical system is the angular, man-made and natural environment represented in three dimensions, and which generates killing grounds not always familiar to soldiers trained in traditional open manoeuvre fields. The functional subsystem is the complex network of transport, communications and utility infrastructure, and the social subsystem is the human dimension to the urban landscape. Rules of engagement delineate the circumstances and limitations under which military forces will initiate and/or continue combat engagement with other forces. Factors are dealing with non-combatants, psychological operations and civil-military liaison, coping with the physical environment, the cultural environment, human issues with equipment, the importance of rules of engagement/status of forces agreement, the potential for including non-lethal weapons in an urban combat system, and the criticality of medical support. In urban operations the nature of the environment is different from that traditionally preferred for manoeuvre warfare. Maintenance of the human will-to-fight depends most on training in basic soldier skills, and skills to use the equipment available, and on leadership, self-discipline and teamwork, all practiced within an urban operating environment. The acquisition of new technology and equipment is important, but secondary.